Indicators of cellular metabolism alterationsin patients with traumatic disease due to hypoxia, depending on a management regimen of intensive care - Matvieienko, M. S.; Volkova, Y. V.; Belozorov, I. V.; Shamoun, K. E.; Riabov, O. V.; Pronin, V. O. (Zaporozhye Medical Journal, 2021)
The aim of this study was to evaluate changes in the level of erythrocyte metabolism under conditions of hypoxia in patients with traumatic disease in polytrauma depending on the components of intensive care (IC). Materials and methods. A prospective study was carried out in 88 patients suffering from polytrauma in the period from 2015 to 2017. All the patients were divided into 2 groups, comparable by severity of trauma and condition. A special feature of the examined patients was the staged surgical correction in all cases according to the Damage Control concept. Patients from the Control group received an intensive care according to the standard local clinical protocol in polytrauma. Patients randomized to the FDP group were treated with infusion of D-fructose-1,6-diphosphate sodium hydrate in addition to the standard care. Hemodynamic parameters and cellular metabolism indicators were monitored: on admission to the operating room, after 24 hours, on day 3, 5 and 14. Results. The signs of hypovolemia were equally severe in both groups on admission to the operating room. The FDP group demonstrated more rapid stabilization of hemodynamics and improved myocardial contractility at the 3rd day of IC. The monitoring of acid-base balance and carbohydrate metabolism showed the presence of compensated metabolic acidosis and energy deficiency. High indexes of lactate/pyruvate indicated a sharp imbalance in the ratio of aerobic/anaerobic metabolic processes. The analysis of ATP dynamics displayed impaired mitochondrial ATP production and inhibition of the glycolytic pathway of energy release. Conclusions. Complementary systemic inflammatory response with the elevation of lactate level by the 5th day occurred in patients with traumatic disease who underwent staged surgical correction. Optimization of intensive care resulted in a faster restoration of the balance between aerobic and anaerobic metabolic processes, an increase in the level of ATP and the rate of 2,3-DPG production in erythrocytes contributing to adequate oxygen supply to the tissues, supporting cellular respiration and preventing the development of oxidative tissue damage, as well as helped to maintain compensatory mechanisms and reduce cellular hypoxia ensuring adequate metabolism of vital organs.